(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
In this article, the concept of competence and its philosophical-pedagogical analysis, the opinions of scientists on this concept are presented, the basic competencies are analyzed, the importance of the competence of subjects (teachers and students) in improving the quality of education is highlighted, and the main factors in the educational system based on the competency approach are mentioned.